Contributions of the Joint Initiative for the Promotion of the One Health Approach in professional and community training to face the Covid-19 pandemic - Rachel, Creuza Rachel; Abou Mourad Ferreira, Mariana; de Oliveira Freitas, Natalia (Guará Journal, 2023)
The  One  Health  approach  integrates  several professionals  to  solve  problems  involving  human,  animal,  and  environmental  health, and its implementation is important for the prevention of  pandemics,  such  as  Covid-19.  This  experience  report  des-cribes  how  our  extension  project  in  One  Health  had  a  positive  impact  on  the  continuity  of  university  activities  during  the  Co-vid-19  pandemic  and  on  the  promotion  of  knowledge  for  the  community  in general.  Due  to  social  isolation,  all  activities  were  carried  out  virtually.  The  tasks,  which  started  in  August  2020,  were:  (i)  webinars  and  meetings  with  professors,  health  professionals,  and  undergraduate  and  graduate  students;  (ii)  international course involving professionals and students from Brazil, Germany,  Mozambique,  and  Kosovo;  and  (iii) dissemi-nation  of  educational  content  in  posts  on social  networks.  We  have done five webinars, 10 study groups to discuss current is-sues, more than 70 content on social media, and two editions of the international course on One Health. The project succeeded in  uniting and  training  a  range  of  professionals  from  different areas of activity, states, and countries, and in disseminating the One Health approach to the general population.
Keywords: One health; Interdisciplinary; Pandemic; Education; COVID-19